Baccharis dracunculifolia D.C: diversidade genética e química de populações - Rigotti, Marcelo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The species Baccharis dracunculifolia, popularly known as rosemary-of-field, is widely used in folk medicine. The form of infusion of its leaves is used for liver problems, stomach disorders and as anti-inflammatory. Studies have reported the use of medical and religious rosemary-of-field sold in markets and fairs in Rio de Janeiro, as well as the use of leaves for wounds and the use of branches as decoction as antipyretic. This study aimed to characterize the chemical composition of essential oils and genetic diversity of native species B. dracunculifolia DC (Asteraceae) in the Cerrado biome. Were collected, on average, 30 individuals from four natural populations, one in Botucatu, in the state of São Paulo, a city of Delfinópolis in the state of Minas Gerais and two in Dourados and Itahum, state of Mato Grosso do Sul. The chemical composition of essential oil extracted by hydrodistillation, was analyzed by gas chromatography coupled with mass spectrometer. The majority of accessions collected substances were trans-nerolidol, cis-β-guaieno, germacrene-D, trans-caryophyllene, limonene, α-pinene, β-myrcene, delta-cadinene, β-pinene and spathulenol. These components amounted to an overall average of 80.97% of the chemical composition of essential oils in four locations. According to the analysis results of the substance trans-nerolidol was the most outstanding among which the present compounds in the essential oil of the species B. dracunculifolia in all populations. However, the accessions were collected in Itahum spathulenol as major components followed by the trans-nerolidol. The study of genetic diversity was performed by analyzing the DNA polymorphism using microsatellite markers. Five microsatellite loci were tested for the species revealed 48 alleles for the four populations ...

A espécie Baccharis dracunculifolia, popularmente conhecida como vassoura ou alecrim-do-campo, é amplamente utilizada na medicina caseira. A infusão de suas folhas é empregada para problemas hepáticos, disfunções estomacais e como anti-inflamatória. Estudos de literatura relatam o uso medicinal e religioso do alecrim-do-campo comercializado em mercados e feiras livres no Rio de Janeiro, assim como a utilização das folhas para feridas e o uso dos ramos, em decocto, como antifebril. Este trabalho objetivou a caracterização da composição química do óleo essencial e diversidade genética da Baccharis dracunculifolia D.C. (Asteraceae) nativa do bioma Cerrado. Foram coletados, em media, 30 indivíduos em quatro populações naturais, sendo uma em Botucatu, estado de São Paulo, uma em Delfinópolis, no estado de Minas Gerais e duas em Dourados e Itahum, estado de Mato Grosso do Sul. A composição química do óleo essencial, extraído por hidrodestilação, foi analisada por meio de cromatógrafo a gás acoplado a espectrômetro de massas. As substâncias majoritárias dos acessos coletados foram trans-nerolidol, cis-β-guaieno, germacreno-D, trans-cariofileno, limoneno, α-pineno, β-mirceno, delta-cadineno, β-pineno e espatulenol. Esses componentes perfizeram uma média geral de 80,97% da composição química dos óleos essenciais nas quatro localidades. De acordo com a análise dos resultados a substância trans-nerolidol foi a que mais se destacou dentre os compostos presentes no óleo essencial da B. dracunculifolia em todas as populações. Entretanto, os acessos coletados em Itahum tiveram como componente principal o espatulenol seguido do trans-nerolidol. O estudo da diversidade ...
Baccharis dracunculifolia D.C.: chemical and genetic diversity of populations
Keywords: Diversidade genética; Plantas aromaticas; Marcadores moleculares; Genetica de populações; Populations genetics